2004
DOI: 10.1055/s-2004-827197
|View full text |Cite
|
Sign up to set email alerts
|

Roles of Ginsenosides on Morphine-Induced Hyperactivity and Rewarding Effect in Mice

Abstract: Ginsenosides, the main effective components of the root of Panax ginseng, have been reported to modulate morphine action. In the present study, ginsenosides Rd, Rb2, Rgl and Re were divided into two groups according to their effects in mice on morphine-induced hyperactivity and conditioned place preference (CPP). Ginsenosides Rd, Rb2, Rgl had no effect on morphine-induced hyperactivity, but antagonized morphine-induced CPP. On the contrary, ginsenoside Re increased morphine-induced hyperactivity whereas it sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 7 publications
(14 reference statements)
0
5
0
Order By: Relevance
“…(1998c, 1999a) showed that ginseng total saponin did not produce an effect at 50 and 100 mg/kg ip. Guo et al . (2004) found that the ginsenosides Rb2, Rd, Rg1 and Re (0.5 and 1 µmol/kg po) and 1:1:1:1 or 1:1:1:2 mixtures of these compounds did not produce an effect.…”
Section: Studies Using Systemic Drug Treatmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…(1998c, 1999a) showed that ginseng total saponin did not produce an effect at 50 and 100 mg/kg ip. Guo et al . (2004) found that the ginsenosides Rb2, Rd, Rg1 and Re (0.5 and 1 µmol/kg po) and 1:1:1:1 or 1:1:1:2 mixtures of these compounds did not produce an effect.…”
Section: Studies Using Systemic Drug Treatmentsmentioning
confidence: 99%
“…(1998c) showed that ginseng total saponin (50, 100 mg/kg ip) blocked morphine (5 mg/kg ip)‐induced CPP. Guo et al . (2004) reported that morphine (5 mg/kg sc)‐induced CPP was blocked by the ginsenosides Rd, Rg1 and Rb2, but not Re (0.5 and 1 µmol/kg po).…”
Section: Studies Using Systemic Drug Treatmentsmentioning
confidence: 99%
“…Their chemical and pharmacological properties have been reported by investigators in many countries. Recently, several studies suggest that Panax ginseng (PG) and its ginsenosides can act on the central dopaminergic system [7,13]. Many studies have also reported that Panax ginseng inhibited the hyperactivity and the conditioned place preference of morphine, cocaine, and methamphetamine [9][10][11].…”
mentioning
confidence: 99%
“…Ginsenosides Rh2, Rg3, and compound K have been reported for apoptosis [16] , [17] and anticancer [18] , [19] , [20] , anti-inflammatory [21] , [22] , and antidepressant-like effects [23] . Previous reports indicated that ginsenosides with different structures have antagonizing properties in the regulation of morphine-induced reinforcement [24] . Despite the potential effects of ginsenosides on morphine dependence and tolerance reported so far, little is known regarding the effects of red ginseng extract (RGE) on morphine-induced behavioral disorders.…”
Section: Introductionmentioning
confidence: 99%